The sea wolf - London, Jack, 1876-1916. (New York : Bantam Books, 1960)
A thrilling epic of a sea voyage and a complex novel of ideas, The Sea-Wolf is a standard-bearer of its genre. It is the vivid story of a gentleman scholar, Humphrey Van Weyden, who is rescued by a seal-hunting schooner after a ferryboat accident in San Francisco Bay. London uses Van Weyden's ordeal at the hands of a schooner's devious crew to explore powerful themes of ambition, courage, and the innate will to survive. The Sea-Wolf also introduces Jack London's most memorable, fully realized character, Wolf Larsen, the schooner's brutal captain, who ruthlessly crushes anyone standing in his way. As Gary Kinder states in his Introduction, " Wolf Larsen is one of the most carefully carved characters in American literature....London, himself, seems as fascinated as the reader with his own creation."
U
b
b